Connective branding : building brand equity in a demanding world - Fisher-Buttinger, Claudia (Wiley, 2008)
This book bridges the gap between strengthening the 'employee brand' and the building 'external brand image' by synthesizing the two approaches. The result is a blurring of the boundaries and assigning creative powers to both. A customer has a number of interactions with the company, and each of these interactions has an impact on the brand equity account - either positive or negative. Examples of interactions include: the product itself, the purchasing process, the consumption experience, the 'face' of the organization, the call center, media etc. The real issue for the company is how to tran.